2021
DOI: 10.3390/nano11040896
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and ε-τ Phase Transformation in MnAl-Based Nanocomposite Magnets

Abstract: Melt spun ribbons of Mn53Al45C2 and Mn52Al46C2 have been synthesized by rapid quenching of the melt with the purpose of monitoring the ε-τ phase transformation to show technologically feasible ways to increase magnetic parameters and to illustrate the viability of these alloys as the next generation of rare earth (RE)-free magnets. By differential scanning calorimetry (DSC), activation energies and temperatures of onset of the ε-τ phase transformation were obtained. Structural analysis was performed using X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In our previous paper [48], we have demonstrated that partial replacement of Mn with small carbon addition was justified on the one hand by the need of obtaining a microstructure where carbon atoms act as nucleation centres for the formation of ordered L1 0 type phase in MnAl, and on the other hand to facilitate the occurrence of a magnetic interaction of the super-exchange type, where the exchange interaction between adjoining MnAl ordered grains/regions is intermediated and facilitated by carbon atoms, mostly situated in the interphase boundaries between neighboring ferromagnetic L1 0 regions/grains.…”
Section: Sem Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In our previous paper [48], we have demonstrated that partial replacement of Mn with small carbon addition was justified on the one hand by the need of obtaining a microstructure where carbon atoms act as nucleation centres for the formation of ordered L1 0 type phase in MnAl, and on the other hand to facilitate the occurrence of a magnetic interaction of the super-exchange type, where the exchange interaction between adjoining MnAl ordered grains/regions is intermediated and facilitated by carbon atoms, mostly situated in the interphase boundaries between neighboring ferromagnetic L1 0 regions/grains.…”
Section: Sem Resultsmentioning
confidence: 94%
“…Structural studies by means of X-ray diffraction have shown [48] that for the two ribbons in the as-cast state, the ε hexagonal phase predominates. This result confirms the hints we have received from the scanning electron microscopy images, i.e., that the two samples are mostly single phased.…”
Section: Xrd Resultsmentioning
confidence: 99%
“…This peak is related to the ετ phase transition, in agreement with the values reported in literature for melt‐spun ribbons. [ 13,28 ]…”
Section: Resultsmentioning
confidence: 99%
“…τ phase transition, in agreement with the values reported in literature for melt-spun ribbons. [13,28] Comparatively to the DSC results, the relative electrical resistance variation (R=R 0 ) in function of the sample temperature using the in-house-built device is also shown in Figure 1. The R 0 value is defined as the initial electrical resistance while R is the resistance at the given sample temperature.…”
Section: Temperature-induced ε ! τ Phase Transitionmentioning
confidence: 97%
“…Nanomagnets, with strong magnetic properties and small volume, have been considered to be the key materials to magnetic and electronic devices that exhibit important applications in artificial intelligence, intelligent robots, wind turbines, and electromobiles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Compared with rare-earth-based nanomagnets, the rare-earth-free nanomagnets earn more attention for their high chemical stability and low cost [ 13 , 14 , 15 , 16 ]. However, these rare-earth-free nanomagnets present small coercivity due to their relatively low magnetocrystalline anisotropy.…”
Section: Introductionmentioning
confidence: 99%